STUDENTS' MATHEMATICAL CREATIVE THINKING: A SYSTEMATIC LITERATURE REVIEW WITH BIBLIOMETRIC ANALYSIS - Farman, Farman; Juniati, Dwi; Khabibah, Siti (Universitas Sembilanbelas November Kolaka, 2022)
This study aims to determine the trend of publications on creative thinking in mathematics learning published on Google Scholar in the 2017-2021 period, as well as describe opportunities and directions for research on creative thinking with themes related to future mathematics learning. This research is a systematic literature review study with bibliometric analysis. This research method uses PRISMA 2020 steps. The study results show that the most productive authors are Asikin, Mulyono and Tohir, each publishing two articles. The paper that gets the most citations is by Hasanah and Surya, which discusses students' creative thinking skills in mathematics using cooperative and problem-solving learning. Research themes such as students, creative thinking, problems and mathematics, and mathematical domains such as numbers, algebra and geometry have been widely used. This allows future research paths that can be studied, including the domain of mathematics in the material of statistics and opportunities, students' creative thinking in 7th and 9th-grade students gender, and the use of technological media to improve or measure students' mathematical creative thinking processes. However, the domains and topics that have been studied are still possible to be reviewed as an effort to maximize students' mathematical creative thinking abilities.